Enhancement of Low pH Stress Tolerance in Anthocyanin-Enriched Transgenic Petunia Overexpressing RsMYB1 Gene - Naing, Aung H.; Lee, Deuk B.; Ai, Trinh N.; Lim, Ki B.; Kim, Chang K. (Frontiers in Plant Science, 2018)
We investigated whether the presence of anthocyanins in plants could contribute to low pH stress tolerance using anthocyanin-enriched transgenic petunia lines (PM2, PM6, and PM8) expressing RsMYB1 and wild-type (WT) plants. We examined several physiological and biochemical factors and the transcript levels of genes involved in abiotic stress tolerance. A reduction in plant growth, including plant height and fresh weight, was observed when plants (PM2, PM6, PM8, and WT) were exposed to low pH (pH 3.0) conditions compared to growth under normal (pH 5.8) conditions. A small reduction in the growth of PM6 was observed, followed by that in PM2, PM8, and WT, reflecting the anthocyanin levels in the plants (PM6 > PM2 and PM8 > WT). An analysis of physiological and biochemical factors also supports the degree of low pH tolerance in the plants (PM6 > PM2 and PM8 > WT). In addition, an enhanced expression of the genes [superoxide dismutase (SOD), catalase (CAT), peroxidase (POX), osmotin, and vacuolar H+-ATPase (V-ATPase)] was observed in the transgenic lines (PM2, PM6, and PM8). The resultant of the enhanced transcript levels of the genes could promote antioxidant activities, proline content, and pH homeostasis involved in the mechanisms underlying abiotic stress tolerance in plants. These results suggest that anthocyanin-enriched plants overexpressing RsMYB1 enhances low pH stress tolerance by elevating the transcript levels of the relevant genes.